Clone-Specific Response in Leaf Nitrate Reductase Activity among Unrelated Hybrid Poplars in relation to Soil Nitrate Availability - Julien Fortier; Benoit Truax; France Lambert; Daniel Gagnon; Normand Chevrier (International Journal of Forestry Research)
In this field study, we used in vivo NRA activity in hybrid poplar leaves as an indicator of NO3- assimilation for five unrelated hybrid poplar clones. We also examined if leaf NRA of these clones is influenced to the same extent by different levels of soil NO3- availability in two riparian agroforestry systems located in pastures. Leaf NRA differences of more than one order of magnitude were observed between the clones, clearly showing their different abilities to reduce NO3- in leaves. Clone DxN-3570, a P. deltoides x P. nigra hybrid (Aigeiros intrasectional hybrid), always had the highest leaf NRA during the field assays. This clone was also the only one to increase its leaf NRA with increasing NO3- soil availability, which resulted in a significant Site x Clone interaction and a positive relationship between soil NO3- concentration and NRA. All of the four other clones studied had one or both parental species from the Tacamahaca section. They had relatively low leaf NRA and they did not increase their leaf NRA when grown on the NO3- rich site. These results provide evidence that NO3- assimilation in leaves varies widely among hybrid poplars of different parentages, suggesting potential preferences for N forms.